Maintaining proteostasis under mechanical stress. (26th July 2021) - Höhfeld, Jörg; Benzing, Thomas; Bloch, Wilhelm; Fürst, Dieter O; Gehlert, Sebastian; Hesse, Michael; Hoffmann, Bernd; Hoppe, Thorsten; Huesgen, Pitter F; Köhn, Maja; Kolanus, Waldemar; Merkel, Rudolf; et al.
Abstract: Cell survival, tissue integrity and organismal health depend on the ability to maintain functional protein networks even under conditions that threaten protein integrity. Protection against such stress conditions involves the adaptation of folding and degradation machineries, which help to preserve the protein network by facilitating the refolding or disposal of damaged proteins. In multicellular organisms, cells are permanently exposed to stress resulting from mechanical forces. Yet, for long time mechanical stress was not recognized as a primary stressor that perturbs protein structure and threatens proteome integrity. The identification and characterization of protein folding and degradation systems, which handle force‐unfolded proteins, marks a turning point in this regard. It has become apparent that mechanical stress protection operates during cell differentiation, adhesion and migration and is essential for maintaining tissues such as skeletal muscle, heart and kidney as well as the immune system. Here, we provide an overview of recent advances in our understanding of mechanical stress protection. Abstract : Cells are constantly subjected to mechanical stress. This review discusses how chaperone and protein degradation systems handle force‐unfolded proteins to preserve protein homeostasis in mechanically stressed cells and tissues.